The Development of Electronic Book Contained Scientific Literacy in Learning Physics to Enhance Students’ Academic Achievement - Muhammad Arifuddin; Andi Ichsan Mahardika*; Fauzia Dwi Sasmita; Syaidah Mahtari (Jurnal Pendidikan Sains Indonesia, 2023)
Technology-based teaching materials enriched with scientific literacy are not yet available, notably regarding the topic of Newton's law of gravity. This study aims to develop e-booster and describe its validity, practicality, and effectiveness. This study uses ADDIE development model with the research subjects consisting of 38 students of X MIPA at a public high school in Banjarmasin. The data collection technique is implemented through interview, observation, questionnaires, and tests. The data analysis is carried out by examining the percentages of the validity test, the average scores obtained from the survey results, as well as the results of the N-gain test and t-test on students’ academic achievements. The results indicated that: (1) the validity test result of e-booster obtained 88.71% which was categorized as very high (2) the practicality result of e-booster obtained 75.39% which was categorized as practical, and (3) the effectiveness of e-booster in improving student’s learning achievement obtained 0.57 which was categorized as moderate and significant at the level α=0.05. It is then concluded that e-booster is valid, practical, and effective, and thus, suitable to be integrated within learning physics to enhance students’ academic achievement